STRATEGI PENGEMBANGAN USAHATANI JERUK MANIS (Citrus sinensis) DI KECAMATAN MANDUAMAS KABUPATEN TAPANULI TENGAH (Studi Kasus: Desa Muara Tapus) - Sunarso, Hendra; Rahmat, Nur (Agros Journal of Agriculture Science, 2023)
Indonesia is an agricultural country that is rich in abundant natural resources, especially agricultural products. Horticultural commodities, especially vegetables and fruit, play an important role in food balance, one of which is sweet orange. The aim of reviewing the Sweet Orange Farming Development Strategy is to be able to increase production by optimally utilizing local human resources (HR) and natural resources (SDA), namely (1) identifying and evaluating the internal and external environment of sweet orange farming which are the strengths and weaknesses. weaknesses, opportunity factors and threat factors. The method used is SWOT analysis and internal factors that influence the development of sweet orange farming are the availability of land and appropriate agro-climatology, farmer experience, availability of labor, availability of agricultural production inputs, the size of sweet orange farming land available. increasingly narrow and the managerial capabilities of farmers are weak. Meanwhile, external factors that influence the development of sweet orange farming are the high demand for sweet oranges, the large number of processed products from sweet oranges, fluctuating prices and the increasingly bad climate and poor road transportation infrastructure and facilities. Based on the results of research using the SWOT strategy matrix, 15 strategies were created using all internal and external factors, and based on the results of the QSPM matrix, the alternative strategy used was to increase production and better quality to meet market needs. 10 sweet orange farmers in Muara Tapus Village were used as respondents. Internal factors and external factors greatly influence the development of sweet orange farming in Manduamas District, Central Tapanuli Regency. Keywords: Strategy, SWOT, Sweet Orange Farming Business. INTISARIIndonesia merupakan negara agraris yang kaya akan sumber daya alam yang melimpah, terutama hasil pertanian. Komoditas hortikultura khususnya sayuran dan buah-buahan memegang bagian terpenting dari keseimbangan pangan salah satunya adalah buah  jeruk Manis. Tujuan mengkaji Strategi Pengembangaan Usahatani Jeruk Manis agar mampu meningkatkan produksinya dengan memanfaatkan sumber daya manusia (SDM) dan sumber daya alam (SDA) lokal secara optimal, yaitu (1) mengidentifikasi dan mengevaluasi lingkungan internal dan eksternal usahatani jeruk manis yang menjadi faktor kekuatan dan faktor kelemahan, faktor Peluang dan faktor ancaman.Metode yang digunakan adalah analisis SWOT dan analisis QSPM, faktor internal yang berpengaruh dalam pengembangan usahtani jeruk manis adalah tersedianya lahan dan agroklimatologi yang sesuai, pengalaman petani, ketersediaan tenaga kerja, ketersediaan input produksi pertanian, luas lahan usahatani jeruk manis yang semakin sempit serta kemampuan manjerial petani yang lemah. Sedangakan faktor eksternal yang berpengaruh dalam pengembangan usahatani jeruk manis adalah permintaan jeruk manis yang tinggi, banyaknya produk olahan dari jeruk manis, harga yang fluktuatif serta iklim yang semakin buruk dan prasarana dan sarana transportasi jalan yang kurang baik. Berdasarkan hasil penelitian dengan menggunakan matriks SWOT stragegi yang dihasilkan sebanyak 15 strategi yang dibuat dengan menggunakan seluruh faktor internal dan faktor eksternal, dan berdasarkan hasil matriks QSPM alternatif strategi yang digunakan adalah meningkatkan produksi dn kualitas yang lebih baik untuk memenuhi kebutuhan pasar. 10 orang petani jeruk manis di Desa Muara tapus dijadikan sebagai responden. Faktor internal dan faktor eksternal sangat berpengaruh terhadap Pengembangan Usahtani Jeruk Manis di Kecamatan Manduamas Kabupaten Tapanuli Tengah. Kata Kunci :Strategi, SWOT,Usahatani Jeruk Manis.